A new Lindley distribution with location parameter. Issue 17 (1st September 2016) - Abd El-Monsef, M. M. E.
Abstract: The Lindley distribution has been used recently for modeling lifetime data and studying some stress-strength problems. In this paper, a new three-parameter Lindley distribution is introduced. The added location parameter offers more flexibility in fitting some real data against other common distributions. Several statistical and reliability properties are discussed. A simulation study has been carried to examine the MSE, bias, and coverage probability for the parameters. A real data set is used to illustrate the flexibility of the proposed distribution.